Use of marine microalgae in bioremediation of palm oil mill effluent - Ang, May Yen (2008)
Malaysia is the largest producer and exporter of palm oil products in the world for the last ten years. The state of Sabah is the leading producer in Malaysia, with a total production capacity of 24 million tones of Fresh Fruit Branch (FFB) per annum. Despite the fact that this industry does contribute to the development of the country, it also generates huge amount of agro-industry wastes that endangers the environment. General treatment often involved biological degradation which is not efficient in reducing the inorganic pollutants. It is possible to utilize marine microalgae to further treat secondary treated Palm Oil Mill Effluent (POME) by using the inorganic pollutants as a nutrient source to produce valuable live feed for aquaculture. Preliminary study on effects of temperature and salinity on growth of three important aquaculture microalgae; proved Isochrysis sp. as the best species as it has the highest specific growth rate, μ = 0.84 day-1 (at 23°C, 30 ppt). This species is known for their suitability for continuous culture. This species was cultured in f/2 in a photo-bioreactor in two different photoperiods (12:12 h and 24:0 h) with the light intensity of 200 μmol-2sec-1. It was observed that the growth rate and crude protein was lower in the 12:12 h photoperiod while there was an increase of lipid by 49%. The overall total fatty acid per gram of sample was doubled in 12h photo-period with a 40.2 % increase of Docosahexaenoic Acid (DHA) and traces of Eicosapentaenoic Acid (EPA) that was not detected in the 24:0 h culture. Based on this finding, 12:0 h photo-period was deduced as the suitable photo-period to produce quality Isochrysis sp. Secondary treated POME was collected and pre-digested anaerobic and aerobically separately before formulation of alternative media. 5% of aerobically treated POME with 0.075% of inorganic NPK fertilizer in seawater gives optimum growth with similar growth with that of standard f/2 in the photo-bioreactor. The harvested biomass showed promising increase of lipid (19.1%) and fatty acids (91%). The pollutants were also successfully reduced; orthophosphate (87%), nitrate (38%), total nitrogen (39%) and BOD (21.3%). The outdoor 10L culture was also promising as it provides a cheaper means for bioremediation and production of quality biomass. Reductions in pollutants were similar with the photo-bioreactor. The outdoor culture Isochrysis sp. had a gross biomass production of 91.7mg/m2/day. The produced biomass had a slight increase in lipid while individual fatty acids concentrations only differ about 30% from the indoor photo-bioreactor. The feeding of rotifer with a combination of alternatively outdoor grown Isochrysis sp. with Nanochloropsis sp. improves and helps prevent the rotifer cultures from crashing.